The Digital Revolution In Recruitment: Unraveling The Impact And Challenges Of E-Recruitment - Mr. Malaykumar Dineshbhai Solanki; Dr. Prakash Gujarati (Educational Administration: Theory and Practice, 2024)
Nowadays, the Internet’s influence has completely changed the way that hiring is done. Thus, the use of the Internet has significantly altered HR recruitment over the past ten years, as well as how organizations view recruiting strategies. Online hiring and candidate recruitment will continue to grow and explode in the upcoming years. Numerous businesses use erecruitment to post job openings, accept resumes, and email applicants. The primary drivers of e-recruitment success are the value-added services offered by the job sites, which include costeffectiveness, speed, customized solution provision, relationshipbuilding with HR managers, and ease of company branding. Another unique aspect is cost-effectiveness, which lowers the initial expenses associated with traditional marketing strategies while reaching a more targeted audience. The hiring process is streamlined by the ability to quickly sort through a large pool of applicants using advanced search and filtering tools, which increases the efficiency of e-recruitment. In addition to its associated benefits, e-recruitment has certain drawbacks. The main objective of this study is to examine the different variables that could affect e-recruitment.